Front Cover, Volume 40, Issue 10. Issue 10 (27th September 2019) - Cox, Timothy C.; Lidral, Andrew C.; McCoy, Jason C.; Liu, Huan; Cox, Liza L.; Zhu, Ying; Anderson, Ryan D.; Moreno Uribe, Lina M.; Anand, Deepti; Deng, Mei; Richter, Chika T.; Nidey, Nichole L.; et al.
Abstract : Front Cover : The cover image is based on the RESEARCH ARTICLE Mutations in GDF11 and the extracellular antagonist, Follistatin, as a likely cause of Mendelian forms of orofacial cletiing in humans by Timothy C. Cox et al., https://doi.org/10.1002/humu.23793 . Cover image © Timothy Cox Images.